Kegiatan Berani Tampil Ceria (BETARIA) Dalam Rangka Pembinaan Kemandirian Siswa SDN 02 Kota Bengkulu - Novela, Rieke; Juarsa, Osa; Agusdianita, Neza (JURIDIKDAS, 2024)
The "Berani Tampil Ceria" (Betaria) activity is a program or series of events held at SD Negeri 02 Kota Bengkulu every Thursday morning from 07:30 to 08:00. This activity provides students with the opportunity to perform in front of an audience, enhance their self-confidence, and develop their speaking and communication skills. Therefore, the research aims to describe how the Betaria activity contributes to fostering independence among students at SD Negeri 02 Kota Bengkulu. The study uses a descriptive research design with qualitative methods. The research subjects are teachers and students of SD Negeri 02 Kota Bengkulu. Data collection techniques include observation, interviews, and documentation. Data credibility is ensured through source triangulation. Data analysis involves data reduction, data presentation, and drawing conclusions. The research results indicate that the fostering of independence carried out by teachers during the Betaria activity consists of four themes: Indonesian language in the first week, arts in the second week, English language in the third week, and religious theme in the fourth week. The Betaria activity follows the stages of planning, implementation, and evaluation. The conclusion drawn from this research is that fostering through the Betaria activity can cultivate a sense of independence in students. Students who have undergone the fostering of independence through Betaria have shown several indicators of independence, such as having a good work ethic, resilience, creativity, courage, and responsibility.